2016
DOI: 10.1039/c6ra16604k
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of Rh-decorated pristine, B-doped and vacancy defected graphene for hydrogen adsorption

Abstract: Rh adatom stability on graphene, with and without defects has been investigated by density functional theory (DFT). The feasibility to achieve uniform dispersion for the metallic atom and the hydrogen storage capacity for each system were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…This work is based on DFT simulations carried out using the Perdew–Burke–Ernzerhof (PBE) functionals ,, and plane-wave ultrasoft pseudopotential implemented in the CASTEP code. , The lattice constants of the graphene model were first fully optimized with a 20 Å vacuum slab. A 5 × 5 × 1 supercell was investigated with a Brillouin zone k -point mesh of 4 × 4 × 1. , The plane-wave basis set was limited to a 380 eV energy cutoff. The convergence tolerance of energy was taken as 10 –5 eV/atom, and the maximum allowed force and displacement were set as 0.03 eV/Å and 0.001 Å, respectively. , The spin-polarized option was lifted for the pristine as well as the defective graphene. Atoms of graphene and adsorbate were relaxed during geometry optimization and transition-state search. Transition states were studied using the linear synchronous transit/quadratic synchronous transit (LST/QST) method .…”
Section: Computational Detailsmentioning
confidence: 99%
“…This work is based on DFT simulations carried out using the Perdew–Burke–Ernzerhof (PBE) functionals ,, and plane-wave ultrasoft pseudopotential implemented in the CASTEP code. , The lattice constants of the graphene model were first fully optimized with a 20 Å vacuum slab. A 5 × 5 × 1 supercell was investigated with a Brillouin zone k -point mesh of 4 × 4 × 1. , The plane-wave basis set was limited to a 380 eV energy cutoff. The convergence tolerance of energy was taken as 10 –5 eV/atom, and the maximum allowed force and displacement were set as 0.03 eV/Å and 0.001 Å, respectively. , The spin-polarized option was lifted for the pristine as well as the defective graphene. Atoms of graphene and adsorbate were relaxed during geometry optimization and transition-state search. Transition states were studied using the linear synchronous transit/quadratic synchronous transit (LST/QST) method .…”
Section: Computational Detailsmentioning
confidence: 99%
“…To describe isolated adatoms adsorbed onto the host graphene, we must consider that simulations at room temperature have shown that adatoms adsorbed on the surface of graphene can be moved from one position to another, being two minima corresponding energy to the adatom in the center of the hexagon benzene or adatom located a bridge site. In both positions, graphene preserves its flatness, with fewer distortions in the geometry of the C-C bonds near the adatom adsorbed ( [34] and [35]). In general, almost all heavy atoms are likely to hybridize at the hollow site, and most of them hybridize with graphene via s, d or f orbitals [36].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In the case of dispersion forces the DFT-D2 Grimme method was considered such as are suggested in the Ref. [36,42], where Van der Waals interactions are described via a simple pair-wise force field, optimized for several popular DFT functionals [43]. The minima of the total energy were found using a conjugate gradient (CG) algorithm.…”
Section: Computational Modelmentioning
confidence: 99%
“…The present calculations show that the Rh adsorption on defective SWCNT is significantly improved by the presence of oxygen on the SWCNT surface. The case of multiple vacancies is not considered because previous studies indicated that Rh adsorption is thermodynamically more stable on single vacancies [36]. The obtained results, report for the first time the induced magnetic moment and changes in the work function and band gap for the adsorbed Rhn cluster on defective (8,0) SWCNT.…”
Section: Introductionmentioning
confidence: 98%